Compound heterozygosity of two novel RHAG alleles leads to a considerable disruption of the Rh complex. Issue 4 (15th April 2016) - Polin, Helene; Pelc‐Klopotowska, Monika; Danzer, Martin; Suessner, Susanne; Gabriel, Christian; Wilflingseder, Julia; Żmudzin, Alicja; Orzińska, Agnieszka; Guz, Katarzyna; Michalewska, Bogumila; Brojer, Ewa
Abstract : BACKGROUND: The Rhesus (Rh) complex consists of a core comprising the Rh proteins (RhD/RhCE) and the Rh‐associated glycoprotein (RhAG) with accessory chains (GPB, LW, CD47). Molecular defects of the RHAG gene may cause a regulator Rhnull phenotype without Rh antigen expression or a Rhmod phenotype with decreased Rh antigen expression. STUDY DESIGN AND METHODS: Blood samples of a donor with strongly diminished Rh antigens and five family members were analyzed by serological phenotyping, flow cytometry, molecular testing, and gene expression analysis of Rh complex candidate genes. RESULTS: RHAG sequencing identified a missense mutation, c.241G>C (p.Gly81Arg) and a splice site mutation, c.640 + 3del14, among the cohort. Compound heterozygosity of these novel alleles identified in the propositus and two siblings gave rise to a strongly diminished expression of RhAG, Rh, and CD47 antigens on the RBC surface. CONCLUSION: The Rhmod phenotype was caused by a novel RHAG splice site mutation in association with a non‐functional allele. The primary depression of RhAG is most likely due to posttranslational events that affect the interaction and processing of the RhAG glycoprotein and gave rise to a secondary depression of RhD, RhCE, and CD47, the major members of the Rh complex.